IMPROVED DETECTION AND DIAGNOSIS OF POLYPOIDAL CHOROIDAL VASCULOPATHY USING A COMBINATION OF OPTICAL COHERENCE TOMOGRAPHY AND OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 9 (September 2019) - Cheung, Chui Ming Gemmy; Yanagi, Yasuo; Akiba, Masahiro; Tan, Anna; Mathur, Ranjana; Chan, Choi Mun; Yeo, Ian; Wong, Tien Y.
Abstract : Purpose: To assess the ability of optical coherence tomography (OCT) alone and in combination with OCT angiography (OCTA) to differentiate polypoidal choroidal vasculopathy (PCV) from neovascular age-related macular degeneration, as compared to fluorescein angiography and indocyanine green angiography. Methods: This is a cross-sectional study. All participants had a standardized history, clinical examination including measurement of best-corrected visual acuity, slit-lamp biomicroscopy, and indirect fundus examination, and underwent standardized imaging (color photography, fluorescein and indocyanine green angiography, OCT, and OCTA) after predefined protocols. We used a 2-step approach (Step 1: spectral domain OCT; Step 2: addition of OCTA) combining structural OCT and OCTA to differentiate 50 treatment-naive eyes with PCV, choroidal neovascularization, and retinal angiomatous proliferation and compared with the diagnosis based on fluorescein angiography and indocyanine green angiography. Spectral domain OCT signs used to diagnose PCV included presence of two out of three of any retinal pigment epithelium detachment (pigment epithelial detachment/double-layer sign), notched or narrow-peaked pigment epithelial detachment, or round subretinal pigment epithelium structure. Optical coherence tomography angiography signs used to diagnose PCV included presence of a localized subretinal pigment epithelium hyperflow signal in the cross-sectional OCTA and/or presence of a focal hyperflow sign in en face OCTA based on outer retina slab. Results: Based on fluorescein angiography and indocyanine green angiography, the diagnosis was choroidal neovascularization in 24 eyes, PCV in 23 eyes, and retinal angiomatous proliferation in 3 eyes. Based on spectral domain OCT signs, PCV was diagnosed in 19/23 (82.6%) eyes; however, specificity of OCT was only 51.9%. Cross-sectional OCTA showed a diffuse hyperflow signal in all 24 (100.0%) eyes with choroidal neovascularization, whereas a localized subretinal pigment epithelium hyperflow signal was detected in 19/23 (82.6%) eyes with PCV. En face OCTA only detected a nodular hyperflow signal in 10/23 eyes (43.5%) with PCV. Combination of OCT and OCTA achieved 82.6% sensitivity and 100.0% specificity for differentiating PCV from choroidal neovascularization/retinal angiomatous proliferation. Conclusion: Cross-sectional OCTA is more sensitive than en face OCTA in detecting flow signal in polyps. Combination of structural OCT and OCTA can be used to screen for PCV with a high level of sensitivity and specificity. Abstract : We compared cross-sectional and structural optical coherence tomography angiography in differentiating polypoidal choroidal vasculopathy from neovascular age-related macular degeneration and found that combination of structural optical coherence tomography and optical coherence tomography angiography provides improved accuracy in differentiating polypoidal choroidal vasculopathy from neovascular age-related macular degeneration.